(3YdGbI GdJOQjH GdYbdj HGdJMed GdfaSj dOi GdYHj cQI GdbOe (B: (3HMK hVaj Ydi HYV GfOjI cQI GdbOe ddQGHWI GdhWfjI GdLRGFQjI GdeMJQaI GdGhdi s - (3SYOhf , TYjHs; (3Hf Ycj, eMfO Bcdjs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2022)
(3jgOa GdHMK Edi GdJYQa Ydi GdYdGbI GdEQJHGWjI Hjf GdJOQjH GdYbdj h GdJMed GdfaSj dOi dGYHj cQI GdbOe, hef CLd OQGSI gPG GdehVhY GYJeO GdHGMK Ydi GdefgL GdhUaj HUaJg GdefgL GdefGSH dWHjYI GdHMK hGdPj jbhe HOQGSI GdYdGbGJ GdEQJHGWjI, ceG TedJ YjfI GdHMK Ydi (B80 (3dGYHG jfTWhf aj CQHY aQb ef GdOhQj GdLRGFQj GdeMJQa GdChd dcQI GdbOe, ceG befG HGNJHGQ UOb hKHGJ ebjGS GdJMed GdfaSj h GSJHjGf GdJOQjH GdYbdj Ydi YjfI eJchfI ef (B15 (3dGYHG hbefG HELQGA GdOQGSI GdCSGSjI Ydi (B65 (3dGYHG hgPG bUO GdJMbb ef UMI GdaQVjGJ, hHYO LeY GdHjGfGJ JeJ eYGdLJgG HGSJNOGe HQfGeL GdMReI GdEMUGFjI (B(spss) (3aj MSGH GdeJhSW GdMSGHj, GdGfMQGa GdeYjGQj, heYGed GdGQJHGW HjQShf HYOgG Je GdJhUd Edi GdGSJfJGLGJ GdJGdjI (B: (3hLhO YdGbI EQJHGWjI OGdI EMUGFjG Hjf GdJOQjH GdYbdj h GdJMed GdfaSj dOi dGYHj cQI GdbOe(B. (3hLhO YdGbI EQJHGWjI OGdI EMUGFjG Hjf GdESJQNGA h GdJMed GdfaSj dOi dGYHj cQI GdbOe(B. (3hLhO YdGbI EQJHGWjI OGdI EMUGFjG Hjf GdEfJHGg h GdJMed GdfaSj dOi dGYHj cQI GdbOe(B. (3hLhO YdGbI EQJHGWjI OGdI EMUGFjG Hjf GdJUhQ GdYbdj h GdJMed GdfaSj dOi dGYHj cQI GdbOe(B. s
(3OcJhQGIs
Keywords: (3GdGQTGO GdfaSj GdQjGVjs; (3GdJMed GdfaSjs; (3GdJOQjH GdYbdjs